Yuridis Tindak Pidana Tanpa Hak Membawa Senjata Tajam pada Putusan Nomor 538/PID.SUS/2018/PN.MDN - Bram Candra; Ediwarman Ediwarman; Taufik Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to find out about criminal acts without the right to carry sharp weapons in Medan City and criminal law policies against people without the right to carry sharp weapons in Medan City. This study uses a normative juridical research method with descriptive analysis with a case approach and a statutory approach, then the data analysis is carried out qualitatively. The results of the study indicate that the legal rules regarding the crime of carrying sharp weapons are regulated in the Emergency Law Number 12 of 1951 concerning the Regulation of Sharp Weapons, Law no. 2 of 2002 concerning the National Police of the Republic of Indonesia and Law Number 1 of 1946 concerning Regulations concerning Criminal Law. The driving faktors for the occurrence of criminal acts without the right to carry sharp weapons in the city of Medan are divided into internal faktors and external faktors. The criminal law policy against people who carry sharp weapons in Medan City consists of a penal policy and a non-penal policy where the penal policy is carried out by legally processing the perpetrators, followed by examining the defendant at trial. The non-penal policy is carried out by increasing public awareness through socialization, carrying out strict supervision by increasing raids and patrols, as well as the importance of parents' attention to their children.